MEKANISME CORPORATE GOVERNANCE, ENTERPRISE RISK MANAGEMENT, DAN NILAI PERUSAHAAN PERBANKAN - Bestari Dwi Handayani (Jurnal Keuangan dan Perbankan, 2017)
The purpose of this study was to examine corporate governance mechanism. This study also examines the effect of mediation of ERM on relationships corporate governance mechanism and the value of the company. The population of this research is financial sector companies listed on the Indonesia Stock Exchange. Sample selection using purposive sampling. This study uses path analysis in hypothesis testing and Sobel test for testing mediation ERM. The results of this study indicate that there is significant influence between corporate governance mechanisms (managerial ownership, institutional ownership, independent commissioner and audit committee) with the value of the company. This study provides evidence that ERM mediating influence between institutional ownership, independent directors and audit committee with the company's value, but not significant in mediating the effect of managerial ownership.